PENGARUH IMPLEMENTASI KEBIJAKAN KOMISI PENYIARAN INDONESIA DAERAH SULAWESI TENGAH TERHADAP EFEKTIVITAS LITERASI MEDIA PELAJAR SEKOLAH MENENGAH ATAS NEGERI 1 PALU - Tuscany, Therisia (Katalogis, 2017)
The aims of this study: (1) to determine the simultaneous influence ofÂ  Central Sulawesi Broadcasting Commissionâ€™s policy implementation on the effectiveness of student media literacy at the state Senior High School 1 of Palu, (2) to determine the partial influence of Central Sulawesi Broadcasting Commissionâ€™s policy implementation on the effectiveness of student media literacy at the State Senior High School 1 of Palu. Policy implementation used the theory developed by Edward III (Riant Nugroho, 2008: 447), while the effectiveness used the theory of Steers in Jamin (1985: 45). The type on this study was quantitative research with explanatory survey approach. Population in this study was the students of the State Senior High 1 of Palu amounted to 1087 students, and drawn using random sampling to 92 students. The data collection techniques of this study were observations, questionaires, and documentation, while the techniques of data analysis was the multiple linear regression. The results showed: (1) the simultaneous influence of Central Sulawesi Broadcasting Commissionâ€™s policy implementation on the effectiveness of student media literacy at the state Senior High School 1 of Palu, with the indicators of communication, resource, disposition and bureaucratic structure, had influence number amounted to 0,505 and was at â€œmediumâ€ influence level, (2) the partial influence of Central Sulawesi Broadcasting Commissionâ€™s policy implementation on the effectiveness of student media literacy at the state Senior High School 1 of Palu seen from the dimension of communication was at â€œmediumâ€ influence level amounted to 0,436, the dimension of resources was at â€œmediumâ€ influence level amounted to 0,578, the dimension of disposition was at â€œmediumâ€ influence level amounted to 0,468, while only dimension of bureaucratic structures whose significantly influence the effectiveness of media literacy, that is a â€œstrongâ€ influence level amounted to 0,736.